The departure of the Greeks from Egypt, 1961: the perspective of Greek diplomacy. (April 2021) - Hatzivassiliou, Evanthis
Abstract : The departure of the greater part of the Greek community from Egypt is one of the many sad stories of the post-war Mediterranean. This article focuses upon the reports of the Greek Consul-General in Alexandria, Byron Theodoropoulos, regarding the Egyptian 'Socialist Laws' of summer 1961, which gave the coup de grâce to the Greek community. It argues that the expulsion of the Greeks was part of a wider redistribution of power in the region. This episode, together with similar experiences in other parts of the Mediterranean, evidently cemented the determination of a younger generation of political leaders and diplomats to seek Greece's future in the cosmopolitan, post-nationalist West, rather than in a 'Near East' rife with nationalism and economic failure.